Beauty ideals, social media, and body positivity: A qualitative investigation of influences on body image among young women in Japan. (September 2021) - Ando, Kanako; Giorgianni, Francesca E.; Danthinne, Elisa S.; Rodgers, Rachel F.
Highlights: Media imagery contributes to body image and eating concerns in young women in Japan. Interviews (mainly group) with young women were conducted and qualitatively analyzed. Four themes emerged on media pressures, additive appearance ideals, and ways of resisting, accommodating, or calibrating these pressures. Young women in Japan are increasingly aware of body positive social media content although the movement in Japan is only nascent. Abstract: Body image and eating concerns are prevalent among Japanese young women and result in part from exposure to unrealistic media imagery. In Western contexts, a growing body of research has explored the impact of social media on body image and eating disorder risk, and the potential for body positive media to mitigate these harmful effects. However, similar research in Japan is lacking. The aim of the present study was to qualitatively explore media and social media influences on body image and associated behaviors among young women in Japan, with a specific focus on body positive media content. Female university students in Japan (n = 29) participated in majority group and some individual interviews. Thematic analysis revealed four primary themes: (1) media appearance pressures: additive pressures of Japanese and Western ideals through globalization, (2) criticism of, resistance to, and negotiating appearance ideals, and (3) presence of body positivity in Japan, and (4) media as a background for interpersonal appearance pressures. High pressure towards thinness emerged, perceived as contributing to weight control behaviors that were calibrated to avoid being "unhealthy." Desire for greater body diversity in Japanese media emerged; however, findings suggest body positive messaging is scarce and mainly limited to high-profile celebrities.